New moon : dua cinta / by Stephenie Meyer ; alih bahasa, Lily Devita Sari ; editor, Rosi L. Simamora - Meyer, Stephenie; Simamora, Rosi L.; Devita Sari, Lily (Gramedia Pustaka Utama, 2009)
517 hlm. ; 20 cm.